The living wage / Donald Hirsch and Laura Valadez-Martinez. - Hirsch, Donald; Valadez-Martinez, Laura (Economy, key ideas., 2023)
This short primer traces the origins of the concept of the living wage and seeks to explain its current rise in fortune as an economic instrument with a social objective. It examines its impact on labour markets and wage levels, explores how it has been applied, and assesses whether it is an effective measure for raising living standards.